The high-pressure compressibility of B12P2. (March 2017) - Gao, Yang; Zhou, Mi; Wang, Haiyan; Ji, Cheng; Whiteley, C.E.; Edgar, J.H.; Liu, Haozhe; Ma, Yanzhang
Abstract: In situ high pressure synchrotron X-ray diffraction measurements were performed on icosahedral boron phosphide (B12 P2 ) to 43.2 GPa. No structural phase transition occurs over this pressure range. The bulk modulus of B12 P2 is K O T = 207 ± 7 G P a with pressure derivative of K ' O T = 6.6 ± 0.8 . The structure is most compressible along the chain formed by phosphorus and boron atoms in the crystal structure. It is believed that the compressibility of boron-rich compounds at close to ambient pressure is determined by the boron icosahedral structure, while the inclusive atoms (both boron and non-boron) between the icosahedra determine the high-pressure compressibility and structure stability.